1998
DOI: 10.1093/sleep/21.2.138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sensory Stimulation on REM Sleep Duration

Abstract: Previous experiments have demonstrated that auditory (AS) and/or somatosensory (SS) stimulation can increase the duration of REM sleep periods in rats, cats and humans. The objectives of this study were to determine whether repeated AS stimulation causes habituation to the stimulus and whether any additive effects could be obtained with the simultaneous application of AS and SS. Three experimental procedures were used in this study. In experiment 1, animals were recorded for 4 consecutive days with AS, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…Previous studies in animal models have reported controversial findings on transient increases (Drucker‐Colin et al ., 1983) or decreases (Mouze‐Amady et al ., 1986; Suntsova et al ., 2000) in phasic activity upon stimulation during REM sleep. Our findings support a phasic to tonic transition in response to acoustic stimuli, which can be explained by switching to a higher level of arousal with raised sensitivity to environmental changes, followed by subsequent re‐established phasic REM activity (Vazquez et al ., 1998; Suntsova et al ., 2000; Voss, 2004). This mechanism may also explain the high dropout rate of usable fMRI trials in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies in animal models have reported controversial findings on transient increases (Drucker‐Colin et al ., 1983) or decreases (Mouze‐Amady et al ., 1986; Suntsova et al ., 2000) in phasic activity upon stimulation during REM sleep. Our findings support a phasic to tonic transition in response to acoustic stimuli, which can be explained by switching to a higher level of arousal with raised sensitivity to environmental changes, followed by subsequent re‐established phasic REM activity (Vazquez et al ., 1998; Suntsova et al ., 2000; Voss, 2004). This mechanism may also explain the high dropout rate of usable fMRI trials in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…For microdialysis studies aiming to characterize changes in transmitter release as a function of sleep, cat is a logical choice because of the long duration NREM sleep and REM sleep epochs compared to rat or mouse. REM sleep epochs in cat last, on average, five to eight min (Ursin, 1968; Baghdoyan et al ., 1984; Lydic et al ., 1987; Vazquez et al ., 1998), thus permitting collection of dialysis samples during periods comprised entirely of REM sleep. Recent studies using cat have demonstrated that ACh release in the substantia innominata region of the basal forebrain is significantly greater during REM sleep than during wakefulness and NREM sleep (Vazquez & Baghdoyan, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In light of results from such studies, any hypotheses concerning effects of longerduration light administration on REM sleep must be regarded with caution. However, a study using auditory stimulation for varying durations and across multiple sleep periods in rats (45) indicated that there was no habituation effect to this stimulus, suggesting that further increases in REM sleep may be possible with more prolonged (or altered schedules) of photic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have indicated that intense cognitive activity or visual stimulation before sleep onset increases REM sleep (6,43). In addition, a handful of studies in mammals (2,8,28,29,45), including one report in humans (33), indicates that various sensory stimuli administered during sleep result in acute REM-sleep enhancement.…”
mentioning
confidence: 99%